Computation of flexural deflection in beams using Clapeyron’s work equality - Selvam, V.K. Manicka; Bindhu, K.R. (Journal of Structural Engineering, 2024)
Knowledge of deflection of structures is necessary for successful design of structures. In the literature, many procedures are available. These methods have advantages as well as limitations. In this note, Clapeyron’s work equality is described for evaluating deflection in beams. It gives either exact or very accurate solution depending upon the shape functions used. It is found that the method is elegant, powerful and efficacious.